ROLE OF DEEPANA PACHANA KARMA IN MANAGEMENT OF RASAPRADOSHAJA VIKARAS - Ashrita S; Shivaprasad Hudeda (International Journal of Ayurveda and Pharma Research, 2020)
For a tree to stand erect with its branches, its roots must be strengthened by nourishing them timely such that the whole tree receives proper nourishment for its growth and development. Similarly, the Tridoshas, Saptha Dhatus and Tri-Malas are the roots strengthening this body when nourished timely. The Dosha-Dhatu-Mala in their state of normalcy enhances the strength of the body which is inferred through their respective physiological functions. This is achieved under the influence of two factors that is- Ahara and Agni. Ayurveda has endowed the function of thermogenesis and metabolism in the body to Agni. Proper functioning of Agni is responsible for all the metabolic activities in the body. Thereby, Agnimandya is said to be the root cause for all the diseases, as it results in the formation of Ama affecting the Rasavaha Srotas initially. The Ama Lakshanas resemble with the Rasapradoshaja Vikaras. Kapha Dosha is said to be the Asrayee in Rasa Dhatu and thereby the Rasa Vruddhi Lakshanas are similar to that of Kapha Vruddhi Lakshanas. So the Chikitsa as mentioned for Kapha Dosha can be implemented in Vruddhi/Kshaya of Rasa Dhatu. Shodhana without Ama-Pachana results in further complication. Therefore the line of treatment revolves around Srotoshodhana, Pachana, Agnideepana and Vatanulomana.